فعالية برنامج تدريبي سلوكي للأمهات لخفض اضطراب الحذف والإبدال لدى أطفالهن من المعاقين عقليا القابلين للتعلم - حنور، قطب عبده خليل; أبوحلاوه، لمياء علي سعد; العطار، محمود مغازي (جامعة كفر الشيخ - كلية التربية, 2021)
هدفت الدراسة إلى التعرف على فعالية برنامج تدريبي سلوكي للأمهات لخفض اضطراب الحذف والإبدال لدي أطفالهن من المعاقين عقليا (القابلين للتعلم)، واستمرار فعالية البرنامج بعد فترة المتابعة لدى عينة قوامها (12) طفل وطفلة من المعاقين عقليا (القابلين للتعلم) ممن تتراوح أعمارهم (8-12) سنوات بمتوسط عمري (10.53)، وانحراف معياري (1.40)، وتم تقسيمهم إلي مجموعتين (ن=6)، وضابطة (ن=6)، واستخدمت الدراسة استمارة البيانات الأولية (إعداد الباحثة)، ومقياس ستانفورد بينيه العرب للذكاء (ط4) تعريب وتقنين أ. د/ مصري عبد الحميد حنوره (2001)، ومقياس كفاءة النطق المصور (إعداد أ. د / إيهاب الببلاوي،2004)، والبرنامج التدريبي السلوكي (إعداد الباحثة)، توصلت الدراسة الحالية إلى وجود فروق دالة إحصائيا بين متوسطات رتب درجات المجموعتين التجريبية والضابطة من أطفال المعاقين عقلياً القابلين للتعلم ذوي اضطرابات النطق في القياس البعدي لاضطراب الحذف والإبدال لصالح المجموعة التجريبية، ووجود فروق دالة إحصائيا بين متوسطات رتب درجات المجموعة التجريبية من أطفال المعاقين عقليا القابلين للتعلم من ذوي اضطرابات النطق في القياسين القبلي والبعدي لاضطراب الحذف والإبدال لصالح القياس البعدي في الاتجاه الأفضل، وعدم وجود فروق دالة إحصائيا بين متوسطات رتب درجات المجموعة التجريبية من أطفال المعاقين عقليا القابلين للتعلم من ذوي اضطرابات النطق في القياسين البعدي والتتبعي لاضطراب الحذف والإبدال بعد مرور شهر ونصف من تطبيق البرنامج.
The study aimed to identify the effectiveness of a behavioral training program for mothers to reduce omission and substitution disorders among their mentally handicapped children (Educable), and the continuation of the program’s effectiveness after the follow-up period for a sample of (12) children with mental disabilities (Educable) between the age of (8 - 12) years with an average age (10,53), and standard deviation (1,40) they were divided into two groups: (experimental N = 6) and (control N = 6). The study used the primary data form (prepared by the researcher), The Stanford Binet Arab Intelligence Scale (SB 4) translated ad legalized by professor Masry Abdel Hameed Hanoura (2001), the pictorial proficiency scale (prepared by professor Ihab Albeblawy 2004), and the behavioral training program (prepared by the researcher). The results of the data analysis and the existence of statistically significant differences between the experimental and control groups in the post-measurement of omission and substitution disorders in favor of the experimental group (in the best direction), and the presence of statistically significant differences between the mean scores of the experimental group's scores in the pre and post measurements omission and substitution disorders in favor of the post measurement, There were no statistically significant differences between the mean scores of the experimental group in the posterior and tracer measures of omission and substitution disorders after one and a half months of applying the program.
Keywords: البرامج التدريبية -- اضطرابات النطق -- اضطراب الحذف والإبدال -- الإعاقة العقلية